ANALISIS PERLAKUAN AKUNTANSI PADA PEMBIAYAAN MUSYARAKAH MUTANAQISHAH DI BANK SYARIAH INDONESIA (BSI) CABANG PANGKALPINANG - Marsita Lara; Muh. Misdar; Atika Atika (Budgeting: Jurnal Akuntansi Syariah, 2021)
The purpose of this study was to determine the accounting treatment of PSAK 106 regarding musyarakah or musyarakah mutanaqishah financing contracts at Bank Syariah Indonesia (BSI) Pangkalpinang Branch. And to find out the suitability of the application of the musyarakah mutanaqishah financing contract at the Indonesian Islamic Bank (BSI) Pangkalpinang Branch with the Statement of Financial Accounting Standards (PSAK) 106. The type of this research is descriptive qualitative. This research was conducted at Bank Syariah Indonesia (BSI) Pangkalpinang Branch. Data collection techniques consist of observation, documentation and interviews. While the data analysis technique consists of data collection, data reduction, data presentation and drawing conclusions. The results of this study indicate that the accounting treatment at the Indonesian Islamic Bank (BSI) Pangkalpinang Branch related to recognition and measurement and disclosure is in accordance with PSAK 106. Meanwhile, the accounting treatment at the Indonesian Islamic Bank (BSI) Pangkalpinang Branch for Musyarakah financing in its presentation is not in accordance with PSAK 106. Because Bank Syariah Indonesia (BSI) Pangkalpinang Branch presents cash and assets as musyarakah receivables, whereas based on PSAK 106 paragraph 35 states that cash or assets delivered to active partners are presented as musyarakah investments.